A Simplified Design for Biodiesel Production. Issue 1 (April 2021) - Ayoola, A.A.; Alagbe, E.E.; Agboola, O.; Ayeni, O.A.; Adeyemi, G.A.; Nnabuko, D.; Makinwa, T.A.
Abstract: In this research work, a simple design for the production of 1kg biodiesel involving two stage esterification-transesterification process, with the use of waste soybean oil (WSO) and NaOH catalyst was considered. CHEMCAD 7.1.2 software was used for the design operation which revealed that four (4) pumps, four (4) heaters, two (2) mixers, one (1) drying equipment and two (2) reactors were involved. Also, the production process design revealed that 0.0513kg/hr of methanol and 0.1800kg/hr of 0.1M H2SO4 were required during the esterification process. While 0.6921kg/hr of methanol, 0.9870kg/hr of WSO as well as 0.1934kg/hr of NaOH catalyst were needed for the transesterification process. The simplicity of the design and high purity level of the biodiesel produced adjudged the design operation good.